SYNTHESIS, SPECTRAL, AND PHARMACOLOGICAL EVALUATION OF 3 AND 5 SUBSTITUTED 2,4-THIAZOLIDINEDIONE DERIVATIVES - Singh Sethi, Navjot; Prasad, Dn; Bhagwat, Deepak; Kumari, Anuradha; Sharma, Madhu; Kaundal, Sangeeta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Background: 2,4-Thiazolidinedione derivatives was launched as antidiabetics in 90's. Later the derivatives of 2,4-thiazolidinedione were banned due to hepatotoxicity. To the date, much research has been directed toward the synthesis and novel uses of 2,4-thiazolidinedione compounds. Aim: The aim of the present study is to synthesize a set of 3,5-disudstituted-2,4-thiazolidinediones as antimicrobial. These compounds were evaluated for their antimicrobial activity. Method: First, the 2,4-thiazolidinedione was substituted at the position of 3 using sodium hydroxide and ethanol and then substituted at the position of 5 in the presence of piperdine by the Knoevenagel condensation method. The structures of the compounds were established on the basis of infrared and nuclear magnetic resonance spectral studies. Result: 3,5-disubstituted-5-benzylidine-2,4-thiazolidinediones derivative was synthesized using benzyl halides and aromatic aldehydes. The results obtained showed that TZ-1 exhibited good activity against Bacillus subtilis while no activity against Escherichia coli. Conclusion: Attachment of more heterocyclic rings containing Nitrogen on the 3rd position of 2,4-thiazolidinedione can enhance the antimicrobial activity. Addition of more lipophilic agents may increase the bioavailability and efficacy of the drug. Long alkyl chains on the benzylidene ring can also increase the lipophilic character, and further attachment of these kind of agents on benzylidene chain may produce safe and effective compounds in future.